Novel poly(vinylidene fluoride-co-hexafluoro propylene)/polyethylene oxide based gel polymer electrolyte containing fumed silica (SiO2) nanofiller for high performance dye-sensitized solar cell - Zebardastan, N. (Elsevier, 2016)
Novel gel polymer electrolytes (GPEs) are prepared using poly(vinylidene fluoride-co-hexafluoro propylene) copolymer (PVdF-HFP) and polyethylene oxide (PEO) in presence of fumed silica nanofiller with the designated system of PVdF-HFP:PEO:EC:PC:NaI:SiO2:I2. GPEs are examined using electrochemical impedance spectroscopy (EIS) and the highest ionic conductivity of 8.84 mS cm−1 is achieved after incorporation of 13 wt.% of fumed silica (SiO2). Temperature-dependent ionic conductivity study confirms that GPE system follows Arrhenius thermal activated model. GPEs are characterized for structural studies using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy. GPEs are used to fabricate dye-sensitized solar cells (DSSCs) and tested under 1 Sun irradiation, obtaining the highest energy conversion efficiency of 9.44% after the incorporation of 13 wt.% fumed silica. Cyclic voltammetry has been performed to analyse electrochemical properties of gel polymer electrolytes.